Metabolic basis of obesity - Ahima, Rexford S. (Springer New York, 2010)
The obesity epidemic has generated immense interest in recent years due to the wide-ranging and significant adverse health and economic consequences that surround the problem. Much attention has been focused on behaviors that lead to obesity, in particular to over consumption of energy-dense food and to sedentary lifestyle. However, obesity is an extremely complex condition with poorly defined pathogenesis. Thanks to greatly enhanced research in the area, the discovery of pathways in the brain and peripheral organs that mediate energy homeostasis has provided a framework for understanding the biological basis of obesity. Metabolic Basis of Obesity adds an important new dimension to the growing literature on obesity by offering a comprehensive review of specifically how metabolic imbalance culminates in obesity. Developed by a team of expert authors, this important title discusses the principles of energy balance, genetics of body weight regulation, hormones and adipokines, and metabolic pathways in the brain, liver, muscle and fat, to name just several of the areas covered. The book also examines the connection between obesity and diabetes, cardiovascular disease and other complications. Current and future diagnostic and treatment strategies are also reviewed. Comprehensive and timely, Metabolic Basis of Obesity is an essential reference for understanding the burgeoning problem of obesity.